Chronic Exposure to Oral Pathogens and Autoimmune Reactivity in Acute Coronary Atherothrombosis. (25th February 2014) - Burazor, Ivana; Vojdani, Aristo
Abstract : Background . It has been hypothesized that various infective agents may activate immune reactions as part of the atherosclerotic process. We aimed to investigate the interrelationship between chronic exposure to oral pathogens and immune-inflammatory response in patients with acute coronary atherothrombosis. Patients and Methods . The study included 200 participants from Serbia: 100 patients with acute myocardial infarction (MI), and 100 age- and sex-matched controls. Antibodies to oral anaerobes and aerobes were determined as well as autoantibodies to endothelial cells, beta-2 glycoprotein I, platelet glycoprotein IIb/IIIa and anticardiolipin. Interleukin-6 (IL-6) and C-reactive protein (CRP) were measured. Results . The mean serum antibodies to oral anaerobes tended to be higher among subjects with MI (0.876 ± 0.303 versus 0.685 ± 0.172 OD, P < 0.001 ). Similarly, antibody levels against oral aerobes in patients were significantly different from controls. Antibodies against endothelial cell, beta-2 glycoprotein I, platelet glycoprotein IIb/IIIa, anticardiolipin along with CRP and IL-6 were highly elevated in patients. The levels of antibodies to oral bacteria showed linear correlation with tissue antibodies, CRP and IL-6. Conclusion . Antibody response to chronic oral bacterial infections and host immune response against them may be responsible for the elevation of tissue antibodies and biomarkers of inflammation which are involved in acute coronary thrombosis development.